The politics of Orthodox churches in the European Union - Leuştean, Lucian 1967- (2018)
This article focuses on the political mobilisation of Orthodox churches in the making of the European Union from the 1950 Schuman Declaration until today. It examines the first contacts between Orthodox churches and European institutions, the structure of religious dialogue, policy areas of Orthodox engagement in the European Union, and competing visions of Europe in the Orthodox commonwealth. It argues that the response of Orthodox churches to the institutionalisation of religious dialogue in the European Union (Article 17 of the Lisbon Treaty) is comparable to that of other religious communities. However, the political mobilisation of Orthodox representations in Brussels advances a geopolitical and civilisational dimension which places the Eastern Orthodox world as a competitor to the secular West.
Keywords: Charta Oecumenica; Commission of the Bishops' Conferences of the European Union (COMECE); Committee of Representatives of Orthodox Churches to the European Union (CROCEU); Conference of European Churches (CEC); Eastern Orthodoxy and secular West; Orthodox engagement in the EU; Symphonia; World Council of Churches (WCC); 'Soul for Europe'